Peran Puslatbang PKASN LAN dalam Pengembangan Sumber Daya Manusia Aparatur Sipil Negara untuk Mendorong Peningkatan Pelayanan Publik - Pranawa, Widyawan (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2024)
The issue of insufficient skills and capacity among employees, even at the managerial level, who are ineffective in managing public services, has been a persistent problem since the early reform era. This study examines the amendments to Law Number 5 of 2014 on Civil Servants (ASN) by the House of Representatives in 2023, which include changes such as a more flexible ASN recruitment process, ease of mobility for high-performing employees, accelerated competency development, and addressing performance issues among employees. These changes inspired the creation of the ASN Corporate University (Corpu). This research utilizes a descriptive qualitative approach with a case study method. The choice of a qualitative approach is based on the need to thoroughly understand and comprehend the phenomenon under study, grounded in HumanResource Development (HRD) theory and the Corporate University concept. The CorporateUniversity at Puslatbang PKASN has successfully implemented programs that have had a positive impact on ASN HR development. It encompasses three key aspects of ASN HR development: Leadership Training, Talent Management, and Competency and Potential Assessment of ASN employees, reflecting concrete efforts in the development of civil servants in Indonesia.